2012
DOI: 10.3390/insects3020378
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Immune Defense Evasion of Selected Inbred Lines of Heterorhabditis Bacteriophora in Two White Grub Species

Abstract: We determined virulence of seven Heterorhabditis bacteriophora strain GPS11 inbred lines possessing superior infective juvenile longevity, and heat and ultra violet radiation tolerance against white grubs Popillia japonica and Cyclocephala borealis. At 1 and 2 weeks after treatment, inbred line A2 was significantly more virulent towards P. japonica compared to the parent strain GPS11 and inbred lines A7, A8, A12 and A21; and line A2 caused significantly higher C. borealis mortality than lines A6 and A12. Penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Once inside the host insect, the nematodes and the multiplying bacteria in the hemocoel produce virulence factors resulting in insect death [8]. Developing nematodes feed on the bacteria by disintegrating host tissues, produce 1-3 generations and when the food resources are exhausted; nematodes emerge as IJs to seek new hosts [9]. During host invasion, the bacteria release several toxins and exoenzymes that play a role in insect death.…”
Section: Introductionmentioning
confidence: 99%
“…Once inside the host insect, the nematodes and the multiplying bacteria in the hemocoel produce virulence factors resulting in insect death [8]. Developing nematodes feed on the bacteria by disintegrating host tissues, produce 1-3 generations and when the food resources are exhausted; nematodes emerge as IJs to seek new hosts [9]. During host invasion, the bacteria release several toxins and exoenzymes that play a role in insect death.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, IJ were likely to escape from the capsule by releasing the bacteria that eventually cause host death. An et al (2012) stated that differences between the virulence of H. bac teriophora inbred lines were related to the ability of ne matodes to break out of encapsulation. Similarly, Li et al (2007) indicated that the immune suppression ability of EPN (S. glaseri in Manduca sexta and H. bacteriophora in Immunity response of Polyphylla adspersa larvae against entomopathogenic nematodes G. mellonella) is correlated with their escape from encap sulation leading to successful infection by nematodes.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, the salient management tool for P. adspersa is the ap plication of chemical insecticides, mainly organophosphates (Radjabi, 1991). Due to concerns related to chemi cal control, an effective, safe and environmentally friendly biocontrol alternative, based on entomopathogenic nema todes (EPN) such as Steinernema scarabaei, S. arenarium, S. glaseri, S. kushidai, Heterorhabditis bacterio phora and H. megidis, is being considered (Klein, 1990;Poinar, 1990;Koppenhofer & Fuzy, 2003;Klein et a l, 2007;An et al, 2012). Among these species, S. glaseri and H. bacteriophora are natu ral pathogens of white grubs (Glaser & Fox, 1930;Poinar, 1990) including P. adspersa .…”
mentioning
confidence: 99%
“…The bacteria can subsequently proliferate in the host causing septicemia, permitting the nematode to develop its life cycle. (An et al 2012 ; Bisch et al 2015 ). Collectively, reports describe some bacteria are capable of eliciting a pathogenic reaction, therefore the host’s immune response acts by encapsulation, phagocytosis, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to that reported in the literature, S teinernema sp3 JCL027 had a greater susceptibility compared with Heterorhabditis efficacy against S. aloeus third instar larvae. We suggest S teinernema sp3 JCL027 IJs were able to overcome the host’s barriers and physiological mechanisms to evade an immune response or digestive tract acidity, permitting the subsequent nematode-bacteria infective cycle development (An et al 2012 ; Demir et al 2014 ). Taking into account Scarabaeidae and Melolonthidae immune response defense, in particular during their third instar (Griffin et al 2005 ), we expected S. aloeus would be more susceptible to Heterorhabditis than Steinernematids based on certain advantages (Khatri-Chhetri et al 2011 ; Vashisth et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%